Interest Rate-Savings Nexus: Keynesian-Classical Debate Revisiting in OECD Economies - Abdullah Miraç Bükey (İktisat Politikası Araştırmaları Dergisi)
There are many factors that determine savings, especially income and consumption. However, classical and Keynesian economic theories disagree on how interest rates affect savings. According to classical theory, an increase in interest rates will increase savings, whereas, according to Keynes, it will definitely decrease it. This is because, according to Keynes, savings are a decreasing function of interest rates and an increasing function of income. In this study, the effect of GDP per capita, especially interest rates, on savings is analysed in the context of the disagreement between Classical and Keynesian economic theories by using a static panel data analysis method on a sample of 35 OECD countries. According to the findings of this study, a 1% increase in GDP per capita increases gross domestic savings by approximately 2.25%, whereas a 1-unit increase in interest rate decreases gross domestic savings by approximately 2.26%. In conclusion, in the dispute between mainstream economic theories regarding the interest-savings relationship, Keynesian theory prevails in the context of OECD countries from 1995 to 2021. In this respect, from a macroeconomic policy perspective, the focus should be on increasing total income rather than interest rates to increase savings.